Review of progress on fabrication technology of Mg matrix composites - Chenyang Jiang; Lidong Gu; Hongwei Xiong; Jingya Wang; Liping Zhou; Mingjie Shen; Jie Wang; Tao Ying; Xiaoqin Zeng (Journal of Magnesium and Alloys)
Mg matrix composites (MgMCs) with enhanced mechanical and functional properties, as well as improved elastic modulus, have aroused rising attention from the aerospace, new energy vehicles, and consumer electronics industries. The suitability of the fabrication process is crucial for achieving uniform dispersion of various reinforcing materials within the Mg alloy matrix and for forming strong interfacial bonding. This ensures that the produced MgMCs meet the requirements for fabricating various components with different demands for size and properties. This paper comprehensively reviews the present fabrication methods for MgMCs in four categories: stir casting, external addition methods, in-situ synthesis methods and novel fabrication methods. It comprehensively focuses on the fabrication principles, process characteristics and key parameters optimization of each technology. Through in-depth analysis, their advantages, limitations and applications are evaluated. Meanwhile, the latest research achievements in microstructure control and mechanical performance optimization are explored. Eventually, the development directions of the fabrication methods for MgMCs in the future are also discussed.